Fish Supply Chain Management Strategy Analysis for Warung Tegal (WarTeg) while Covid-19 Policy is Enforced in the Administrative City of South Jakarta - Telaumbanua, Kania Raflesia; Suhana, Suhana; Mulyani, Rita Yuni (Research Synergy Press, 2023)
Warung Tegal is a small, lower-middle class restaurant in Indonesia. The name Warung Tegal, comes from Bahasa Indonesia, where